Moldavan Ethno-Linguistic Identification — The Consequence of the Previous Language Policy: Array - Kiseolar, Polina (Journal of Danubian Studies and Research, 2021)
Ethno-linguistic identification of Romanian speakers in the south of Odessa region is an essential issue. Their ethno-linguistic self-identification is characterized in that most Romanian speakers who lived this area has accepted the ethnonym “Moldovan”. The researching tasks of our study, which is based on the discussions with the interviewed romanophones who live in the south of Bessarabia: - the criteria of Moldovan self-identification compared with Romanian one and vice versa; - what the national language means to Romanians (Moldovans) under independent Ukraine in terms of (a) ethnicity, (b) language function; - how Romanians (Moldovans) from the south of Odessa region understand such terms as “ethnic identity” and “citizenship”; how they identify themselves and how it affects on their linguistic identification; - functional distribution of the languages of romanophones, who speak two or more languages, according to the areas of life or specific situations; the factors which make speaker to switch between languages or use them in alternative ways. The main components of individuation during the process of self-determination of ethnic and language identity are ignorance of historical truth and manipulating ethnic and language awareness of romanophones.